Exploring Attitudes on the Sustainable Balance Between Nature Conservation and Economic Development Through Ecotourism—Lessons from EU and Non-EU Countries - Tamara Gajić; Dragan Vukolić; Ana Spasojević; Ivana Blešić; Marko D. Petrović; Jovan Bugarčić; Marina Bugarčić; Bojana D. Drašković; Milovan Milivojević (Land)
This study examines attitudes toward achieving a sustainable balance in ecotourism using the Stimulus-Organism-Response (SOR) model, focusing on economic and environmental factors shaping sustainable practices. Data were collected from tourists, local residents, and managers in Serbia and Croatia, encompassing diverse perspectives on natural resource conservation, economic benefits, and community engagement. The results indicate that natural resource conservation significantly contributes to local participation, tourist awareness, and community engagement, with notable differences observed among respondent groups. Economic benefits also positively influence these mediating factors, emphasizing their role in achieving sustainability goals. The MGA revealed significant differences between respondent groups, highlighting that managers and local communities in Croatia demonstrated higher levels of awareness and participation compared to Serbia, while differences among tourists were less pronounced. This research contributes to the sustainable tourism literature by integrating perspectives from various stakeholder groups and emphasizing the importance of community involvement and environmental preservation. Practical implications include recommendations for policymakers and managers to develop strategies that encourage stakeholder participation and promote sustainable tourism development.